Immobilization of plasmids in bacterial nanocellulose as gene activated matrix - Poetzinger, Yvette; Rahnfeld, Lisa; Kralisch, Dana; Fischer, Dagmar (Carbohydrate Polymers, 2019)
The synergy of the local delivery of nucleic acids using a hydrogel-based gene activated matrix (GAM) might support regenerative processes on a genetic level by concurrently providing a cell-friendly microenvironment. To investigate bacterial nanocellulose (BNC) as GAM, two plasmids (pSV-β-Gal and pGL3) were incorporated by reswelling and injection techniques forming matrix and core-shell systems as determined by SEM and staining experiments. The release was found to be dependent on the type of BNC, the plasmid and the loading technique, and lasted over at least 20 days. No morphological or mechanical changes of the BNC due to the presence of plasmids were observed. Immobilized plasmids especially in the matrix systems were protected against enzymatic degradation by maintaining the high biocompatibility of BNC and transfection efficacy of the plasmids. These results indicate that BNC can be used as a promising and renewable carrier for the application as local gene delivery system.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Bacterial nanocellulose; Biocompatibility; Controlled release; Gene activated matrix; Gene delivery